2011
DOI: 10.1021/jf2003267
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and Ulcer-Healing Mechanisms of Ellagic Acid in Experimental Rats

Abstract: Ellagic acid (EA), a plant-derived polyphenol, exhibits antioxidant, anti-inflammatory, and gastroprotective effects. Its gastroprotective mechanisms have not been fully elucidated nor have its effects on chronic ulcer previously been described. Toward these ends, the antiulcer activities of EA were evaluated in acute (ethanol and indomethacin) and chronic (acetic acid) ulcer models in Wistar rats. In this study, oral administration of EA significantly prevented the gastric ulceration caused by ethanol, indome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 62 publications
0
50
0
2
Order By: Relevance
“…Reduced TNF-a levels and MPO activity in rats with colonic inflammation [156]. Attenuated TNF-a, interferon-c, and IL-4 and IL-6 levels in rats [157]. Reduced expression of TNF-a, iNOS, COX-2, NF-jB, and IL-6 in rats with colon carcinogenesis [158] Lowered renal levels of TNF-a, IL-6, IL-1b, and MCP-1 in diabetic mice [159].…”
Section: Isoliquiritigeninmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced TNF-a levels and MPO activity in rats with colonic inflammation [156]. Attenuated TNF-a, interferon-c, and IL-4 and IL-6 levels in rats [157]. Reduced expression of TNF-a, iNOS, COX-2, NF-jB, and IL-6 in rats with colon carcinogenesis [158] Lowered renal levels of TNF-a, IL-6, IL-1b, and MCP-1 in diabetic mice [159].…”
Section: Isoliquiritigeninmentioning
confidence: 99%
“…In most studies with human subjects, 154 150-500 mg of curcumin was sufficient to manifest a response, 155 and as little as 150 mg of curcumin has been shown to be effective 156 in reducing serum levels of pro-inflammatory cytokines [35]. Con- 157 sidering the expense and the side effects associated with currently 158 available TNF blockers, this polyphenol represents important ther- 159 apeutics for TNF associated diseases. 160 …”
Section: Introductionmentioning
confidence: 99%
“…Excess production of peroxynitrite can cause hypercholesterolemia, obesity, diabetes mellitus (Drel et al, 2007;Korda et al, 2008;Patcher et al, 2005), gastric ulcer (Beserra et al, 2011), and gastrointestinal disease (Singer et al, 1996). Recently, it was reported that ellagic acid, a potent peroxynitrite scavenger, can prevent gastrointestinal diseases such as gastric ulcer (Beserra et al, 2011) and Crohn's disease (Rosillo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that ellagic acid, a potent peroxynitrite scavenger, can prevent gastrointestinal diseases such as gastric ulcer (Beserra et al, 2011) and Crohn's disease (Rosillo et al, 2011). Furthermore, acetaminophen-inducedor galactosamine/lipopolysaccharide-induced hepatic injuries (Cover et al, 2005;Yokoyama et al, 2009), which are accepted as models in vivo animal experiments, are closely associated with the production of peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacological activities, such as cardiovascular protective activities, antihypertensive effects (with inhibition of serum angiotensin-converting enzyme activity), hypoglycemic effects, and increased high-density lipoprotein (HDL)-cholesterol level, have been revealed. Moreover, anticancer, antibacterial, anti-H. pylori, antiinflammatory (in the gastrointestinal tract), and antiulcer effects have been recently discovered (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%